Epithelial malignancies of Endometrium: 2 years experience at Fatima Memorial Hospital (Journal of Rashid Latif Medical College, 2022)
Objective: Rapidly accumulating sophisticated information highlights thefact that differential diagnosis of endometrial hyperplasia and well differentiated endometrioid adenocarcinoma is complicated not only by the resemblance of these lesions to each other, but also by their tendency to be misdiagnosed. Detailed comprehension of rules and pitfalls in the grading of endometrioid adenocarcinomas and the estimation and reporting of myometrial invasion is of substantial importance to have a better understanding of issue. Study design: A cross- sectional study. Duration of study: Two years. Place of study: Departments of Pathology, Fatima Memorial Hospital. Methods: The study consisted of 27 specimens of endometrial tumors, received fixed in 10% formalin. Haematoxylin and Eosin stained slides were examined to determine the histological type by WHO classification, and immunohistochemistry was done in difficult cases.Results: Majority of these tumors were endometriod adenocarcinomas,Serous tumors 1 clear cell carcinoma 1 and one case of squamous cellcarcinoma in situ. In one cases there is simultaneous tumor in ovary andendometrium. 2 cases have tumor both in cervix and endometrium.Conclusion: Detailed and accurate analysis of patients' tissue as 'deeply' aspossible is necessary to obtain information on morphological background to provide the clinicians with information relevant for individualized medicine